O protagonismo do educando na construção de jogos e sua replicabilidade em sala de aula como instrumento de fixação e recuperação contínua - Escobedo, Mateus Beluca (Universidade Federal de São Carlos, 2016)
This work related about games construction and application in classroom, aiming the development of competence and ability prescribed in Sao Paulo State Curriculum, further helping the continuous fixation and assistance. The topics are Sequences, Progressions and Volumes. Each content was initially worked with chalk and board, and, then, valued. Posteriorly the games were built by the students and applied in classroom. After the perception of necessary changes in one of the games, the adjustments were made and the game was reapplied. The results were satisfactory, further having significant possibility of improvement. The steps of the work are separately reported, from the content choices to be worked, passing throughout didactic engineering (diagnostic assessment, planning, implementation and evaluation) beside the results, in way to favor the proper understanding about the work to provide the review of the importance of games as a relevant factor in mathematics teaching, fixation and knowledge building.
Keywords: Jogos Matemáticos; Progressões; Sequências; Volume; Protagonismo Juvenil; Mathematical Games; Memory Game; Dominoes; Sequences; Progressions; Youthful Protagonism; CIENCIAS EXATAS E DA TERRA::MATEMATICA